1999
DOI: 10.1007/s004410051236
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine regulation of distinct trophoblast functions in vitro by placental macrophages

Abstract: In view of the accumulating evidence for paracrine mechanisms regulating trophoblast function, we tested the hypothesis that placental macrophages affect trophoblast activity in a paracrine fashion. Trophoblast was isolated from 17 term placentas (-IP). One aliquot of cells was further immunopurified (+IP) using an HLA class I antibody. This increased the proportion of trophoblast (+IP >97%; -IP approximately 70%) as identified by rigorous immunocytochemistry. Most (approximately 70%) non-trophoblast cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 32 publications
0
53
0
Order By: Relevance
“…As shown in Figure 8, we observed that our population of isolated EVCT was 97% pure as analyzed by double labeling using antibodies against cytokeratin 7, a specific marker of trophoblast Tarrade et al cells (Cervar et al, 1999), and hPL. In addition, these EVCT cells expressed c-erbB2 (Fig.…”
Section: Immunocytochemical Characterization Of Cultured Evctmentioning
confidence: 62%
See 1 more Smart Citation
“…As shown in Figure 8, we observed that our population of isolated EVCT was 97% pure as analyzed by double labeling using antibodies against cytokeratin 7, a specific marker of trophoblast Tarrade et al cells (Cervar et al, 1999), and hPL. In addition, these EVCT cells expressed c-erbB2 (Fig.…”
Section: Immunocytochemical Characterization Of Cultured Evctmentioning
confidence: 62%
“…During this process, the length of enzymatic digestion, the bath of trypsin used, and the absence of agitation are critical steps to monitor. The different immunocytochemical studies performed on these EVCT confirmed the presence of cytokeratin 7, specifically expressed in the trophoblast cells (Cervar et al, 1999). We also checked the absence of fibroblastic contamination by vimentin immunostaining of immunocompetent cells from the decidua by CD45 and of endothelial cells by antiWillebrand factor immunostaining.…”
Section: Characterization Of Human Trophoblastsmentioning
confidence: 83%
“…Isolation of cells Trophoblasts (TTs) and ECs were isolated from term placentas after uncomplicated pregnancy and vaginal delivery following a standard protocol [12,13]. First-trimester trophoblasts (FTs) were isolated from placental tissue after pregnancy terminations for psychosocial reasons (seventh to tenth week of pregnancy) as described previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…Characterisation and culture of human trophoblasts and ECs All cell preparations were subjected to rigorous immunocytochemical characterisation [12][13][14]. Trophoblasts were tested for viability by measuring secreted human chorionic gonadotropin hormone (hCG) levels using a commercially available assay (Dade Behring, Deerfield, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation